Sonda de capacitância e Hydrus-1D como facilitadores na estimativa dos parâmetros da Equação de Van Genuchten - Nascimento, Ícaro Vasconcelos do (2019)
Hydrus-1D is an inverse model that allows the estimation of soil hydraulic parameters. The hypothesis was: the parametrization of the van Genuchten equation by inverse modeling with Hydrus-1D, using data of temporal variation of the matric potential (obtained by tensiometry) and moisture (obtained by gravimetry and by FDR - Frequency Domain Reflectometry - probe) results in soil-water curves (SWC) as consistent with the field conditions as those obtained in the laboratory. The aim was to obtain the parameters of the van Genuchten model, with Hydrus-1D, using data of the temporal variation of mafic potential (obtained by tensiometry) and moisture (obtained by gravimetric method and FDR probe), as well as in laboratory, to then compare these results. For this, data of matric potential and moisture over the time were obtained in an instantaneous profile experiment, in Fortaleza/CE. Four experimental plots (1.5 x 2.0 x 0.5 m) were assembled with soil from the textural classes loamy-sand and sand. In each plot, an FDR probe (Diviner 2000) access tube was installed, and, apart 0.3 m from the tube, were installed tensiometers with a Hg manometer at depths of 0.2 and 0.4 m. Concomitant to the probe and tensiometers readings, soil samples were collected at each depth. Volumetric moisture was calculated by the product of gravimetric moisture by soil density (in g cm-³).. At the end of the experiment, when the insignificant drainage rate was reached, soil samples with disturbed and undisturbed structure were collected. In the laboratory, analyzes of soil and particle density, porosity and SWC were performed. The SWC were adjusted by the van Genuchten model (with m = 1 / n). With Hydrus-1D, four parameters of the van Genuchten equation (with m = 1 / n) were obtained. The data were analyzed with the completely randomized design 4 x 4 (four experimental procedures and four replicates). The Jarque-Bera test was used to verify normality and Tukey's test for comparison of means, both with p = 0.05. The curves of moisture over the time simulated by Hydrus-1D were also plotted. The performance of the model was evaluated by the coefficient of efficiency and root mean square error. It was concluded that the parametrization of the van Genuchten equation by Hydrus-1D, with moisture data (obtained by gravimetry and by FDR probe), results in SWC as consistent with the field conditions as those obtained in the laboratory; and the use of Hydrus-1D with moisture data obtained with FDR probe is very practical and concise, returning good results and facilitating the process of obtaining the SWC.